HUBUNGAN KUALITAS TIDUR, KONSUMSI ENHANCER DAN INHIBITOR ZAT BESI DENGAN KADAR HEMOGLOBIN REMAJA PUTRI DI SMAN 3 CIBINONG - Devi Afifah Yuliadharma, - (2023)
Anemia is caused by the hemoglobin level and the factor that can affect hemoglobin levels is sleep quality. Anemia also occurs due to a deficiency of iron nutrient intake which is affected by the ability to absorb iron. The absorption of iron intake can be influenced by enhancers and inhibitors. The purpose of this study is to determine the relationship between sleep quality, consumption of iron enhancers, and inhibitors with hemoglobin levels in female adolescents at SMAN 3 Cibinong. This study was an observational study with a cross-sectional design and involved 50 female students in grades X and XI who were selected using stratified random sampling. It was found that the average Hb level of the respondents was 12.7 g/dL. As many as 54% of respondents often consume iron enhancers and 56% of respondents often consume iron inhibitors. There is a relationship between sleep quality and Hb levels (p = 0.024), there is no relationship between consumption of iron enhancers and Hb levels (p = 0.209), and there is a relationship between consumption of iron inhibitors and Hb levels (p = 0.033). So the conclusion is that sleep quality and consumption habits of iron inhibitors can affect Hb levels and trigger anemia so respondents are advised to reduce the consumption of iron inhibitors in an effort to prevent anemia early.